Single camera three component planar velocity measurements, using two frequency Planar Doppler Velocimetry (2v-PDV) (2005) - Charrett, Thomas O. H.; Ford, Helen D.; Tatam, Ralph P. (International Society for Optical Engineering; 1999, 2005)
The work presented here describes a method that allows three component velocity measurements to be made, quickly and non-intrusively, across a plane in a flow defined by a laser light sheet. The method, two frequency planar Doppler Velocimetry (2v-PDV) is a modification of the planar Doppler velocimetry (PDV) technique, using only a single CCD camera, and sequential illumination of the flow using two frequencies, separated by about 700 MHz. One illumination frequency lies on an absorption line of gaseous iodine, and the other just off the absorption line. The beams sequentially illuminate a plane within a seeded flow and Doppler-shifted scattered light passes through an iodine vapour cell onto the camera. The beam at a frequency off the absorption line is not affected by passage through the cell, and provides a reference image. The other beam encodes the velocity information as a variation in transmission dependent upon the Doppler shift. Use of a single camera ensures registration of the reference and signal images, which is the major problem in any spilt image system such as a two-camera imaging head, and cost efficiency is improved by the simplification of the system. A 2v-PDV system was constructed using a continuous-wave Argon ion laser and acousto-optic modulators to produce two frequencies of illuminating laser light. This was combined with multiple imaging fibre bundles, to port three different views of the measurement plane to a CCD camera, allowing the measurement of three velocity components.
Keywords: Planar Doppler Velocimetry, flow measurement, acousto-optic frequency switching